2015
DOI: 10.1002/2015ja021647
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional Hall MHD simulation of lunar minimagnetosphere: General characteristics and comparison with Chang'E‐2 observations

Abstract: Lunar minimagnetosphere formed by the interaction between the solar wind and a local crustal field often has a scale size comparable to the ion inertia length, in which the Hall effect is very important. In this paper, the general characteristics of lunar minimagnetosphere are investigated by three‐dimensional Hall MHD simulations. It is found that the solar wind ions can penetrate across the magnetopause to reduce the density depletion and cause the merging of the shock and magnetopause, but the electrons are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
4
13
0
1
Order By: Relevance
“…Such a multi-dipole effect was also found in the recent Hall MHD simulations done by Xie et al (2015), in which the lunar crustal field was modeled by five dipoles with a surface strength of 480 nT and a mini-magnetosphere could form even near the subsolar region. Furthermore, Xie et al (2015) found that the formation of LMM favors higher SZA and smaller ion inertia length, and the simulation results are consistent with the observations by both LP and Chang'E-2. Additionally, the reflected solar wind ions can help to slow down and compress the solar wind flow, and also play a role in the formation of LMM (Fatemi et al, 2014;Halekas et al, 2014).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Such a multi-dipole effect was also found in the recent Hall MHD simulations done by Xie et al (2015), in which the lunar crustal field was modeled by five dipoles with a surface strength of 480 nT and a mini-magnetosphere could form even near the subsolar region. Furthermore, Xie et al (2015) found that the formation of LMM favors higher SZA and smaller ion inertia length, and the simulation results are consistent with the observations by both LP and Chang'E-2. Additionally, the reflected solar wind ions can help to slow down and compress the solar wind flow, and also play a role in the formation of LMM (Fatemi et al, 2014;Halekas et al, 2014).…”
supporting
confidence: 71%
“…However, later studies showed that the non-dipolar nature of the lunar crustal fields makes them have a larger lateral extent than a dipole, which could enhance the efficiency to stand off the solar wind and reduce the field strength needed to form a mini-magnetosphere (Harnett & Winglee, 2003). Such a multi-dipole effect was also found in the recent Hall MHD simulations done by Xie et al (2015), in which the lunar crustal field was modeled by five dipoles with a surface strength of 480 nT and a mini-magnetosphere could form even near the subsolar region. Furthermore, Xie et al (2015) found that the formation of LMM favors higher SZA and smaller ion inertia length, and the simulation results are consistent with the observations by both LP and Chang'E-2.…”
mentioning
confidence: 78%
“…In addition, some current peaks may be associated with local magnetic anomalies. Lunar magnetic anomalies are thought to be able to prevent the incoming solar wind and reduce the solar wind flux on the lunar surface (Deca et al, 2016; Xie et al, 2015). As a result, they can change the flux of backscattered solar wind and lead to a disturbance in the LDEX current, as discussed by (Walker et al, 2017).…”
Section: Dust Fountain Observed By Ladeementioning
confidence: 99%
“…Numerous investigations have explored the potential mechanisms at work within crustal magnetic anomalies with laboratory experiments [ Wang et al , , ] and numerical simulations, including magnetohydrodynamic (MHD) [e.g., Harnett and Winglee , , ; Xie et al , ], hybrid [ Fatemi et al , , ; Jarvinen et al , ; Giacalone and Hood , ; Poppe et al , ], and kinetic/particle‐in‐cell methodologies [e.g., Poppe et al , ; Deca et al , , ; Zimmerman et al , ; Bamford et al , ]. These simulations have suggested that large‐scale ambipolar and/or Hall electrostatic fields may be the primary mechanism of proton reflection from lunar crustal magnetic fields, rather than magnetic reflection.…”
Section: Introductionmentioning
confidence: 99%